On the Plastic Flow Localization of Martensitic Stainless Steel Saturated with Hydrogen; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Barannikova S. Svetlana; Bochkareva A. V. Anna Valentinovna; Lunev A. G. Alexey Gennadievich; Shlyakhova G. Galina; Li Yu. Yulia; Zuev L. Lev (2016, 2016)
Title screen